PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN ETIKA PERGAULAN SISWA KELAS XI MIPA DI SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2015/2016 - Rizki Suci Ananda; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this study aims at bertujan to find out the influence of group guidance services to increased ethical guidelines for students. This research was conducted from June to August 2016 2016. Research methods used are real methods of experimental with pretest-posttest pattern control group design. The subjects in this research is research grade XI with the ethical guidelines for a low total of 10 students. Data collection instrument used was the now are open. Data analysis technique used was statistics nonparametric techniques. Based on hhasil test of wilcoxon research hypothesis turns out to be accepted IE there is a difference of ethical guidelines for students before and after the implementation of the experimental group guidance and group control based on the test results of the mann-withneyy there is a significant difference of ethical guidelines for students on the Group's experiments with a group control. Spearman Rank test based on the influence of group guidance services against the ethics guidelines for students that is 46.1%.Key Words: Group, Ethical Guidance Service Association.